Developing and Using a Board Game as a Tool for Urban and Social Resilience and Flood Management Planning in the Bangkok Metropolitan Region. (May 2017) - Marome, Wijitbusaba; Pholcharoen, Thitirat; Wongpeng, Natthaphon
Public participation in the development of urban resilience can help create cities that are not only more sustainable but also more fair and inclusive. However, incorporating public inputs in the planning process is difficult for urban practitioners. This article explores the researchers' attempt to develop and utilise a board game as a tool for consolidating urban and social resilience and flood management planning in Bangkok, outlining the challenges and shortcomings that had to be overcome with each revision during the designing process, and the outcomes. The experience suggests that board games, whose development should be an evolving process based on research, could be used as an effective deliberative tool for knowledge exchange, transformative learning and gathering inputs for policymaking.